2017
DOI: 10.1016/j.neuron.2017.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Memory of Morphologies by Septins during Neuron Generation Allows Early Polarity Inheritance

Abstract: Transmission of polarity established early during cell lineage history is emerging as a key process guiding cell differentiation. Highly polarized neurons provide a fascinating model to study inheritance of polarity over cell generations and across morphological transitions. Neural crest cells (NCCs) migrate to the dorsal root ganglia to generate neurons directly or after cell divisions in situ. Using live imaging of vertebrate embryo slices, we found that bipolar NCC progenitors lose their polarity, retractin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 71 publications
1
32
0
Order By: Relevance
“…In epithelial cells, septins associate with subsets of MTs and are required for vesicle transport from the Golgi complex to the plasma membrane (Bowen et al, 2011; Spiliotis et al, 2008). In neurons, septins are involved in the morpho-genesis of axons and dendrites, but it is unknown if they function in polarized membrane traffic into axons and dendrites (Ageta-Ishihara et al, 2013; Boubakar et al., 2017; Hu et al, 2012; Tada et al, 2007; Xie et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In epithelial cells, septins associate with subsets of MTs and are required for vesicle transport from the Golgi complex to the plasma membrane (Bowen et al, 2011; Spiliotis et al, 2008). In neurons, septins are involved in the morpho-genesis of axons and dendrites, but it is unknown if they function in polarized membrane traffic into axons and dendrites (Ageta-Ishihara et al, 2013; Boubakar et al., 2017; Hu et al, 2012; Tada et al, 2007; Xie et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The technique was adapted from (Boubakar et al, 2017b). 18 hours after graft, embryos were harvested in cold HBSS and extra-embryonic membranes were removed.…”
Section: Slice Embryo Culture and Live Imaging Of Nb Grafted Cellsmentioning
confidence: 99%
“…Septins can recognise areas of micron-scale curvature, including the cytokinetic furrow (see Glossary, Box 1 ) and phagocytic cup (see Glossary, Box 1 ), where they act both as scaffolds for protein recruitment and as diffusion barriers for subcellular compartmentalisation ( Saarikangas and Barral, 2011 ; Mostowy and Cossart, 2012 ; Bezanilla et al, 2015 ; Cannon et al, 2017 ). Consistent with this, new work has shown that septins in neurons contribute to cell shape memory ( Boubakar et al, 2017 ) and the maturation of dendritic spines ( Yadav et al, 2017 ).
Fig.
…”
Section: Recent Mechanistic Insights Into Shigella mentioning
confidence: 63%